2022
DOI: 10.3390/plants11030317
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Healthful Flavonoids among Diverse Mandarin Accessions

Abstract: Mandarins have many unique flavonoids with documented health benefits and that help to prevent chronic human diseases. Flavonoids are difficult to measure and cannot be phenotyped without the use of specialized equipment; consequently, citrus breeders have not used flavonoid contents as selection criteria to develop cultivars with increased benefits for human health or increased tolerance to diseases. In this study, peel, pulp, and seed samples collected from many mandarin accessions and their hybrids were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…SNPs rates is directly proportional to the level of diversity, higher the number of SNPs greater the diversity among the citrus species, same as observed in other plants like rice (Terol et al 2008;Mattia et al 2022), Accordingly we hypothesized that the genetic variations reported in Citrus reticulata (present study) might be lower than that of Citrus sinensis, since Citrus reticulata is native to south Asia and most arose as crosses. Within a group such as satsumas there are many varieties that arose as mutants, but Citrus reticulata (broadly defined) includes many sexually produced hybrids.…”
Section: Discussionsupporting
confidence: 66%
“…SNPs rates is directly proportional to the level of diversity, higher the number of SNPs greater the diversity among the citrus species, same as observed in other plants like rice (Terol et al 2008;Mattia et al 2022), Accordingly we hypothesized that the genetic variations reported in Citrus reticulata (present study) might be lower than that of Citrus sinensis, since Citrus reticulata is native to south Asia and most arose as crosses. Within a group such as satsumas there are many varieties that arose as mutants, but Citrus reticulata (broadly defined) includes many sexually produced hybrids.…”
Section: Discussionsupporting
confidence: 66%
“…conducted GWAS analysis of genes responsible for flavonoid biosynthesis of diverse mandarin accessions. 46 Another study by Minamikawa et al. used GWAS analysis to identify putative genetic traits controlling fruit quality.…”
Section: Discussionmentioning
confidence: 99%
“…The large amount of whole genome sequencing data of citrus and relatives enabled GWAS analysis of putative genetic determinants of HLB resistance/tolerance and susceptibility. Mattia and colleagues conducted GWAS analysis of genes responsible for flavonoid biosynthesis of diverse mandarin accessions (Mattia et al, 2022). Another study by Minamikawa et al .…”
Section: Discussionmentioning
confidence: 99%